Detection of Possible Quasi-periodic Oscillations in the Long-term Optical Light Curve of the BL Lac Object OJ 287 - Bhatta, G.; Zola, S.; Stawarz, Ł.; Ostrowski, M.; Winiarski, M.; Ogłoza, W.; Dróżdż, M.; Siwak, M.; Liakos, A.; Kozieł-Wierzbowska, D.; Gazeas, K.; Debski, B.; et al. (The Astrophysical Journal, 2016)
The detection of periodicity in the broadband non-thermal emission of blazars has so far been proven to be elusive. However, there are a number of scenarios that could lead to quasi-periodic variations in blazar light curves. For example, an orbital or thermal/viscous period of accreting matter around central supermassive black holes could, in principle, be imprinted in the multi-wavelength emission of small-scale blazar jets, carrying such crucial information about plasma conditions within the jet launching regions. In this paper, we present the results of our time series analysis of the ∼9.2 yr long, and exceptionally well-sampled, optical light curve of the BL Lac object OJ 287. The study primarily used the data from our own observations performed at the Mt. Suhora and Kraków Observatories in Poland, and at the Athens Observatory in Greece. Additionally, SMARTS observations were used to fill some of the gaps in the data. The Lomb-Scargle periodogram and the weighted wavelet Z-transform methods were employed to search for possible quasi-periodic oscillations in the resulting optical light curve of the source. Both methods consistently yielded a possible quasi-periodic signal around the periods of ∼400 and ∼800 days, the former with a significance (over the underlying colored noise) of ≥slant 99 % . A number of likely explanations for this are discussed, with preference given to a modulation of the jet production efficiency by highly magnetized accretion disks. This supports previous findings and the interpretation reported recently in the literature for OJ 287 and other blazar sources.
Keywords: Accretion; Accretion Disks; Astrophysics - High Energy Astrophysical Phenomena; BL Lacertae objects: individual: OJ 287; galaxies: active; galaxies: jets; radiation mechanisms: non-thermal